2023
DOI: 10.1111/mec.17171
|View full text |Cite
|
Sign up to set email alerts
|

The population bottleneck of the Iberian wolf impacted genetic diversity but not admixture with domestic dogs: A temporal genomic approach

Diana Lobo,
José Vicente López‐Bao,
Raquel Godinho

Abstract: After decades of intense persecution, the Iberian wolf subspecies faced a severe bottleneck in the 1970s that considerably reduced its range and population size, nearly leading to its extinction in central and southern Iberian Peninsula. Such population decline could have impacted the genetic diversity of Iberian wolves through different processes, namely genetic drift and dynamics of hybridization with domestic dogs. By contrasting the genomes of 68 contemporary with 54 historical samples spanning the periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…This, in combination with intensive human driven selective breeding to develop and maintain specific breed traits in more recent periods, have shaped dog genetic diversity through time. Previous studies on wolves have also found past and recent demographic events, including bottlenecks and within and between-species admixture ( Pilot et al 2014 , 2019 , 2021 ; Fan et al 2016 ; Loog et al 2020 ; Bergström et al 2022 ; Lobo et al 2023 ). Even though wolves have not undergone the same human selective breeding as dogs, they have been subjected to a high degree of human induced pressures via habitat loss and systematic persecution ( Wayne et al 1992 ; Fredrickson et al 2007 ; Sastre et al 2011 ; Pilot et al 2014 ; Kuijper et al 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“…This, in combination with intensive human driven selective breeding to develop and maintain specific breed traits in more recent periods, have shaped dog genetic diversity through time. Previous studies on wolves have also found past and recent demographic events, including bottlenecks and within and between-species admixture ( Pilot et al 2014 , 2019 , 2021 ; Fan et al 2016 ; Loog et al 2020 ; Bergström et al 2022 ; Lobo et al 2023 ). Even though wolves have not undergone the same human selective breeding as dogs, they have been subjected to a high degree of human induced pressures via habitat loss and systematic persecution ( Wayne et al 1992 ; Fredrickson et al 2007 ; Sastre et al 2011 ; Pilot et al 2014 ; Kuijper et al 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“…The population increased after partial legal protection in the 1970s ( Valverde 1971 ; Grande del Brío 1984 ; Blanco et al 1992 ) and has been stable for the last 30 years, at around 350 packs or about 2,000 to 2,500 individuals ( MITECO 2016 ; Torres and Fonseca 2016 ). Despite this demographically healthy population condition, population genetic estimates using a small panel of microsatellites suggested an effective population size of about just 50 individuals ( Sastre et al 2011 ), and previous analyses showed a loss of mtDNA diversity during population expansion ( Salado et al 2023 ), and a reduction in genome-wide diversity due to the 1970s population bottleneck ( Lobo et al 2023 ).…”
Section: Discussionmentioning
confidence: 94%
“…The high levels of inbreeding that we observe suggest that inbreeding depression could locally be an issue in modern Iberian wolves if the fragmentation continues in the population. Inbreeding depression has not been documented or suggested in Iberian wolves ( Lobo et al 2023 ), but it is possible that this may simply be due to a lack of data. Relevant data that could be collected include morphological data, behavioral data, and reproductive success since these traits have been shown to be impacted by inbreeding depression in other wolf populations.…”
Section: Discussionmentioning
confidence: 99%